2008
DOI: 10.1016/j.comppsych.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The period of untreated psychosis before treatment initiation:

Abstract: Aim-This study employed a qualitative research methodology to explore common themes pertaining to the period of untreated psychosis prior to treatment initiation in hospitalized, urban, African American, first-episode psychosis patients.Methods-Twelve family members of 10 patients were interviewed at length to gather detailed narrative accounts of factors related untreated psychosis and treatment delay. Using qualitative analysis, verbatim transcripts were reviewed by two researchers to identify prominent them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 34 publications
7
77
0
1
Order By: Relevance
“…The delay in treatment of psychotic symptoms until they reach crisis proportions may be due in part to families’ misattribution of symptoms and behaviors to typical adolescence or to stress or drugs (20,25). Although evolving symptoms may be subtle and nonspecific, this misattribution of symptoms may be due in part to reluctance on the part of patients and families to deal with the stigma of the label of a mental illness (2,12).…”
Section: Discussionmentioning
confidence: 99%
“…The delay in treatment of psychotic symptoms until they reach crisis proportions may be due in part to families’ misattribution of symptoms and behaviors to typical adolescence or to stress or drugs (20,25). Although evolving symptoms may be subtle and nonspecific, this misattribution of symptoms may be due in part to reluctance on the part of patients and families to deal with the stigma of the label of a mental illness (2,12).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature has additionally suggested that DUP is significantly associated with the severity of positive and negative symptoms at the time of presentation.Whereas limited previous reports have supported a link between DUP and grandiosity, bizarreness, 8,9 unusual or dangerous behaviour, 10,11 and avolition and poor social integration, 12 surprisingly little research to date has explored specifically what types of positive and negative symptoms are most associated with the length of untreated psychosis.…”
Section: Introductionmentioning
confidence: 95%
“…For example, among Chinese speaking individuals in Australia with anxiety disorders, the most frequently endorsed reason for seeking out formal services was problem recognition (Ho et al, 2008). Mismatches between “lay” and “expert” diagnoses have been associated with the length of untreated psychosis or other mental health problems (Bergner et al, 2008) and for postpartum hemorrhage documented in rural India (Sibley et al, 2005). While not fully consistent, this research suggests the need to consider controls.…”
Section: Theoretical Backgroundmentioning
confidence: 99%